Travel Pouch: zero waste innovation of courier bag / Nurain Syaqiren Mohd Ja'afar ... [et al.] - Mohd Ja'afar, Nurain Syaqiren; Nor Aspari, Nurul Anis Athirah; Ungku Mizan, Ungku Najihah Izani; Saparrudin, Najib Hakim Harith; Mohd Yunus, Amirul Nazwan (2021)
The use of plastic bags today is seen to be increasing. The increase in the population of the earth has caused a high demand for plastic bags. Just look at today, with the state of the world plagued by an epidemic of covid-19 disease everyone is forced to sit at home for a long period. Most sectors of the economy cannot be physically opened. However, they are turning to online shopping, such as Shopee, Lazada, Zalora, and many more. Therefore, the days will be when there will only be people who shop online causing the demand for parcels to increase until there is a dumping of courier bags. Garbage plastic is also one of the garbage that takes the longest time to decompose. Typically, discarded plastics take up to 1000 years to decompose. While plastic bags take between 10 to 1000 years. As for plastic bottles, the time taken to decompose is more than 450 years (Negara, 2016). To reduce the dumping of courier bags, an idea to use recycled items was undertaken. Our group had planned to make a travel pouch using a courier bag that we got while giving away items online. Ideas like this come when one sees so many unused courier bags after buying goods. Therefore, the travel pouch that we inspired from second-hand items provides many benefits not only to the people around but also to the environment itself.